(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The Nutrition Installation is one of the supporting health services in hospitals. Not only providing services to patients being treated, but nutrition services can also become a revenue center for the continuity of the hospital's business. The Indonesian government has supported the health tourism program as an effort to restore the national economy. In this program, it is hoped that hospital services can also focus on food creations served by the Nutrition Installation and aimed at patients who incidentally are tourists, both local and foreign. Indonesia needs to learn from Thailand, Singapore and Malaysia which have made health tourism a source of economic income through medical, spa and wellness tourism. The role of nutrition services is included in preventive and promotive efforts that can be carried out by hospitals to attract tourists. By paying attention to external and internal focus, a hospital can identify readiness in welcoming health tourism. Collaboration with stakeholders is useful for examining the roles and responsibilities of the nutrition installation and the health worker team. Hospitals also need to understand the concept of the tourism industry to be able to partner with potential clients in marketing hospital nutrition. Various diet menus to traditional herbal medicine can be a strategy in supporting health tourism program efforts. Hospitals need to keep up with the times in order to be able to compete in the midst of a revived economy. The nutrition installation is one that can be developed to assist the government in improving public health with the concept of a new healthy lifestyle.